2022
DOI: 10.1186/s12915-022-01445-6
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in CA1 modulate schema establishment in the hippocampal-cortical neuron network

Abstract: Background Schema, a concept from cognitive psychology used to explain how new information is integrated with previous experience, is a framework of acquired knowledge within associative network structures as biological correlate, which allows new relevant information to be quickly assimilated by parallel cortical encoding in the hippocampus (HPC) and cortex. Previous work demonstrated that myelin generation in the anterior cingulate cortex (ACC) plays a critical role for dynamic paired associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 58 publications
3
17
0
Order By: Relevance
“…At S17 the mean PI reached the maximum level (77%). This result is consistent with the other reports (Tse et al, 2007; Hasan et al, 2019; Liu, S. et al, 2022). However, the hM4Di-CNO group consistently had lower mean PI (Fig.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…At S17 the mean PI reached the maximum level (77%). This result is consistent with the other reports (Tse et al, 2007; Hasan et al, 2019; Liu, S. et al, 2022). However, the hM4Di-CNO group consistently had lower mean PI (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Training rats with several PAs leads to schema formation which is stored in the ACC and the learnt PAs gradually become hippocampus independent (Tse et al, 2007; Tse et al, 2011; Hasan et al, 2019; Liu, S. et al, 2022). Astrocytic G i pathway activation was shown to modulate different cognitive functions (Jones et al, 2018; Kol et al, 2020; Liu, S. et al, 2022). However, the effect of ACC astrocytic G i activation on schema memory is yet unknown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Astrocytes are able to differentiate the activity of discrete synapses that originate from different afferents and modify synaptic activity at surrounding synapses by releasing active substances 22 to modulate various neuronal circuits 30,36,[69][70][71] , and affect behavioural responses 29,38,72,73 . It has been well demonstrated that astrocytes support neuronal functions by regulating the flow of extracellular ions and neurotransmitters, and by providing neuronal energy substrates such as lactate by means of their astrocytic processes.…”
Section: Discussionmentioning
confidence: 99%